PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE PADA PEMBELAJARAN IPA ANAK TUNAGRAHITA SDLB - Andriana Wahyu Istanti; H. A. Triwidjaja (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
The purpose of this research was (1) Describing the applying of Picture and Picture Learning Method In Sains Teaching and Learning Process of the third Grade Mental Retardation Students in SDLB B-C Kepanjen, Malang Regency. (2) Describing the activities of the mild mental retardation students in SDLB B-C Kepanjen while they was applying picture and picture method in sains learning. (3) Describing the result of the mild mental retardation stundents in SDLB B-C Kepanjen after they was applying by picture and picture method.This research use class action research (CAR). The result of the pre-research was 54,29 with learning completeness 29%. In the first cycle was about 64,99 with the class learning completeness was 42,86%. While in the second cycle was about 74,29 with the learning completeness was 85,71%. The conclusion of the research was trough Applying Picture and Picture Learning